Pengaruh Keadilan Distributif, Prosedural, dan Interaksional Terhadap Kepuasan Kerja dan Komitmen Organisasi Pada Paramedis di Rumah Sakit Tk II Udayana Denpasar - Sutrisna, I Wayan Wira; Rahyuda, Agoes Ganesha (E-Jurnal Manajemen; Vol 3 No 9 (2014), 2014)
The aim of this study is to understand the effect of organizational justice on job satisfaction and organizational commitment, and also to understand the role of job satisfaction as mediators on the effects above. Organizational justice created in terms of importance to foster job satisfaction and organizational commitment that will have implications for the optimal paramedic services. The respondents of this study is the paramedics at Level II Udayana Hospital. The total of the respondents is 95 paramedics. The sampling method is proportionate stratified random sampling technique through Slovin formula. The analysis technique used in proving the hypothesis is path analysis and the Sobel test. The results obtained in this study 1) ?? distributive justice , procedural, and interactional positive and significant effect on job satisfaction paramedics, 2) distributive justice, procedural, interactional, and job satisfaction and a significant positive effect on organizational commitment paramedics, 3) job satisfaction significantly mediate the relationship of distributive justice, procedural, and interactional organizational commitment. This study has several limitations that include: 1) the study only see that organizational commitment will be created through a factor of organizational justice and job satisfaction, but did not rule out the emergence of other factors beyond the study, 2) the study focused on the hospital industry means necessary special consideration if this research will be applied in other industries, such as manufacturing and tourism. Keywords: distributive justice, procedural justice, interactional justice, job satisfaction, organizational commitment.
Keywords: distributive justice, procedural justice, interactional justice, job satisfaction, organizational commitment.